Adherence to best care practices in normal birth: construction and validation of an instrument - Elisabete Mesquita Peres de Carvalho; Leila Bernarda Donato Göttems; Maria Raquel Gomes Maia Pires (SciELO, 2015)
Abstract OBJECTIVE To describe the stages of construction and validation of an instrument in order to analyze the adherence to best care practices during labour and birth. METHOD Methodological research, carried out in three steps: construction of dimensions and items, face and content validity and semantic analysis of the items. RESULTS The face and content validity was carried out by 10 judges working in healthcare, teaching and research. Items with Content Validity Index (CVI) ≥ 0.9 were kept in full or undergone revisions as suggested by the judges. Semantic analysis, performed twice, indicated that there was no difficulty in understanding the items. CONCLUSION The instrument with three dimensions (organization of healthcare network to pregnancy and childbirth, evidence-based practices and work processes) followed the steps recommended in the literature, concluded with 50 items and total CVI of 0.98.